Phytochemical compounds from Calophyllum buxifolium Vesque, Calophyllum depressinervosum M.R. Hend. & Wyatt-Sm. and Morinda citrifolia L. and their anti-proliferative activity - Zamakshshari, Nor Hisam (2017)
Plants have been used in folk medicines for treatment of diseases. The stem bark of Buxifolium, Calophyllum depressinervosum and Morinda citrifolia were studied for their phytochemical and biological activities. Different chromatographic methods were used to isolate and purify pure compounds from these three plants species. The structural elucidations of these pure compounds were achieved through FT-IR, UV-Vis, GC-MS, 1D and 2D NMR. Extensive phytochemical studies on three different plants species which are Buxifolium vesque, Calophyllum depressinervosum and Morinda citrifolia have resulted in the isolation of 30 compounds of various classes such as xanthones, coumarins, kavalactones, flavonoids, terpenes and anthraquinone. Morinda citrifolia gave twelve anthraquinones. Meanwhile, Calophyllum depressinervosum and Calophyllum buxifolium gave 12 and 6 phenolic compounds, respectively. Surprisingly, desmethoxyyangonin (88) from the kavalactone class was found in Calophyllum depressinervosum. This is the first report on the existence of kavalactones in Calophyllum species. This research reports the new anti-proliferative activities of the extracts and isolated compounds against three cancer cell lines which are SNU-1 (stomach cancer), LS174T (colon cancer) and K562 (leukemia). The hexane extract of Calophyllum depressinervosum showed strong inhibition activity against SNU-1 with an IC50 value of 9.50 μg/ml. Meanwhile, the hexane extract of Calophyllum buxifolium gave strong inhibition activities against LS174T and K562 cell lines. Caloxanthone B (16) gave the highest inhibition activity compared to the other compounds against SNU-1 and K562 with IC50 values of 1.47 μg/ml and 1.23 μg/ml, respectively. For LS174T, xanthochymone B (86) gave the highest inhibition activity with an IC50 value of 0.45 μg/ml. Structural modifications were successfully carried out on two major compounds (ananixanthone (83) and thwaitesixanthone (21)) isolated from Calophyllum depressinervosum and Calophyllum buxifolium respectively and this resulted in 5 new synthesis compounds. The acetylation on ananixanthone (83) gave two new synthesised compounds which are ananixanthone monoacetate (98) and ananixanthone diacetate (99). Meanwhile, the acetylation on thwaitesixanthone (21) resulted in another new synthesised compound thwaitesixanthone monoacetate (102). Methoxyananixanthone (100) and O-benzylananixanthone (101) were successfully synthesised from ananixanthone (83) through methylation and benzylation reactions. These synthesised compounds were also screened for cytotoxic activity against the SNU-1, LS174T and K562 cell lines to check for any increase in inhibition activity after modification. Unfortunately, only methoxyananixanthone (100) had better inhibition towards LS174T cell line compared to ananixanthone (83) with an IC50 value of 5.76 μg/ml. Antioxidant activity tests on the crude extracts were carried out using five different assays, DPPH, beta-carotene bleaching assays, and ferric reducing antioxidant power (FRAP) assay, nitric oxide scavenging activity and ferrous ion chelating. In the DPPH assay, the methanol extract of Calophyllum depressinervosum gave good antioxidant activity with an EC50 value of 16.02 μg/mL. Meanwhile, the extract with the highest percentage of β-carotene bleaching and comparable to the standard drug was the ethyl acetate extract of Calophyllum depressinervosum which is 72.89% at 100 μg/mL. The FRAP assay that showed the methanol extract from Calophyllum buxifolium possess the highest FRAP value which is 8.19 GAE compared to other extracts. Good nitric oxide scavenging activity was shown by the dichloromethane extract of Morinda citrifolia. Last but not least, the highest chelating effect was shown by the dichloromethane extract of Calophyllum depressinervosum with a percentage of 40.42% at 500 μg/ml. Molecular docking study was attempted to elucidate the mechanisms by which the active compounds could induce anti-proliferative activities in SNU-1, K562 and LS174T. The molecular docking technique was used to model the binding interaction between active compounds and responsible protein chosen from each cancer cell. The responsible protein chosen for SNU-1, K562 and LS174T were HER2, Src and β-catenin respectively. The molecular docking studies showed that all the active compounds could bind well with the responsible protein and could act as anti-cancer inhibitors.